Is it feasible to treat polycystic ovarian syndrome with or without insulin resistance using glucokinase activators as novel hypoglycaemic medications? A protocol for a systematic review and meta-analysis - Xiaojing Liu; Lei Zeng; Shuo Yuan; Genping Zeng; Xijing Lu; Peiyin Li; Tan Zeng; Zitong Lin; Yuxi Miao (BMJ Open)
Introduction A variety of hypoglycaemic drugs are used to treat polycystic ovarian syndrome (PCOS), but their efficacy remains insufficient. Glucokinase activators (GKAs) are a unique class of hypoglycaemic medications with emerging potential, notably in significantly reducing insulin resistance (IR). Nevertheless, the efficacy of GKAs in treating PCOS, particularly in the absence or presence of IR, remains uncertain. The meta-analysis protocol aims to address this knowledge gap, furnish evidence-based data to support potential revisions in PCOS treatment guidelines and promote the utilisation of GKAs in clinical settings.Methods and analysis A comprehensive search will be conducted across the Cochrane Central Register of Controlled Trials, PubMed, Web of Science, Embase, Medline, Scopus, CNKI, Wanfang and VIP databases to identify randomised controlled trials investigating the use of GKAs in the treatment of PCOS, irrespective of the presence of IR. The search will encompass all available studies without language restrictions and cover the period from the inception of each database to 10 April 2024. Disputes will be resolved by talking with a third expert following the screening of articles and data extraction by two reviewers. The primary outcomes of interest encompass changes in anthropometric parameters, menstrual frequency, sex hormone levels, and glucose metabolism, while secondary objectives include lipid metabolism and adverse events. The methodological quality of each study will be assessed using Version 2 of the Cochrane Collaboration tool for assessing Risk of Bias (RoB 2.0), and the Grade of Recommendations, Assessment, Development and Evaluation (GRADE) technique will be used to assess the quality of evidence and degree of recommendation. The study duration of this study will be from 5 April 2024 to 10 April 2025.Ethics and dissemination Since this study just analyses data that are readily available to the public and does not directly involve patient participation, ethical approval is not necessary. The findings will be made public by being published in a medical journal that is subject to peer review.PROSPERO registration number CRD42024535633.